Sosialisasi Undang-Undang Nomor 24 Tahun 2013 Tentang Administrasi Kependudukan Di Desa Jenggik Utara Kecamatan Montong Gading Kabupaten Lombok Timur - Widya Hartati; Salmi Yuniar Bahri; Nova Hari Santhi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Population administration is a series of structuring activities in controlling and publishing population data documents through population registration, civil registration and management of population information and the utilization of the results for public services. Therefore, it is important to carry out socialization activities for Law Number 24 of 2013 so that people are more aware of and obedient to population administration. The method used is to provide outreach, followed by direct service from the DUKCAPIL Office after going through the data collection process. By carrying out this service, the community feels helped because this is the first time an activity like this has been carried out in the village. This adds to the enthusiasm of community members who do not yet have MCH, KTP or making KK and changing KK to immediately take part in the service. This population document is vitally needed by the community and must be kept and protected by the state. Apart from that, the expected results are that the people of Jengdik Utara village are more aware of the importance of the population documents presented during the socialization of Law number 24 of 2013 to achieve complete population administration.